Use of ruthenium complexes for formation and/or hydrogenation of amides and related carboxylic acid derivatives - Milstein, David; Gunanathan, Chidambaram; Ben-David, Yehoshoa; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Zhang, Jing (US20120253042, US20160152663, 2012)
A process for preparing amides by reacting a primary amine and a primary alcohol in the presence of a Ruthenium complex to generate the amide and molecular hydrogen. Primary amines are directly acylated by equimolar amounts of alcohols to produce amides and molecular hydrogen (the only byproduct) in high yields and high turnover numbers. Also disclosed are processes for hydrogenation of amides to alcohols and amines; hydrogenation of organic carbonates to alcohols; hydrogenation of carbamates or urea derivatives to alcohols and amines; amidation of esters; acylation of alcohols using esters; coupling of alcohols with water and a base to form carboxylic acids; dehydrogenation of beta-amino alcohols to form pyrazines and cyclic dipeptides; and dehydrogenation of secondary alcohols to ketones. These reactions are catalyzed by a Ruthenium complex which is based on a dearomatized PNN-type ligand of formula A1 or precursors thereof of formulae A2 or A3.